Sub-District Government Bureaucracy and Public Services Performance During the COVID-19 - Cendy Rahmawaty; Desfitha Maharani Putri; Herman Lawelai; Nastia Nastia; Anwar Sadat (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2022)
The purpose of this study was to analyze the performance of the Sub-District government bureaucracy and public services during the COVID-19 pandemic. The results of this study indicate that in terms of Government Bureaucratic Performance in the Middle of the COVID-19 Pandemic in Lea-Lea Sub-District, employees understand and can carry out their duties and functions as state servants in carrying out public services during the COVID-19 pandemic. This can be seen from the ability to provide services starting from Input Indicators, Process Indicators, Output Indicators, Result Indicators, Benefit Indicators, and Impact Indicators. This is supported by observations and in-depth interviews with officers on duty at the Lea-Lea Sub-District office, who complained about the lack of supporting facilities and infrastructure during the COVID-19 outbreak.